2014
DOI: 10.1016/j.neulet.2014.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Neuroglobin overexpression improves sensorimotor outcomes in a mouse model of traumatic brain injury

Abstract: There is a significant need for novel treatments that will improve traumatic brain injury (TBI) outcomes. One potential neuroprotective mechanism is to increase oxygen binding proteins such as neuroglobin. Neuroglobin has a high affinity for oxygen, is an effective free radical scavenger, and is neuroprotective within the brain following hypoxia and ischemia. The purpose of this study was to determine whether neuroglobin overexpression improves sensorimotor outcomes following TBI in transgenic neuroglobin over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 30 publications
(52 reference statements)
2
23
0
3
Order By: Relevance
“…Thus, despite the fact that we have not been able to monitor the CmNgb early (that is to say from the installation of the initial symptomatology until admission to the service), our results support the idea that elevation of CmNgb is a function of the duration of stroke [11] [53]. This elevation of Ngb in the acute phase of stroke may be explained by the ischemic nature of the initial lesion and/or because stroke (ischemic or hemorrhagic) is usually complicated by initial or secondary cerebral ischemia, with cell lysis, favoring the progressive overexpression of Ngb at the cerebral level and secondarily the release in the plasma [24] [53]. In this case, this result suggests CmNgb as a biological element of monitoring, at least during the early and critical phase of stroke [11] [12] [13].…”
Section: Cmngb and Mean Of Age Of The Working Populationsupporting
confidence: 83%
See 2 more Smart Citations
“…Thus, despite the fact that we have not been able to monitor the CmNgb early (that is to say from the installation of the initial symptomatology until admission to the service), our results support the idea that elevation of CmNgb is a function of the duration of stroke [11] [53]. This elevation of Ngb in the acute phase of stroke may be explained by the ischemic nature of the initial lesion and/or because stroke (ischemic or hemorrhagic) is usually complicated by initial or secondary cerebral ischemia, with cell lysis, favoring the progressive overexpression of Ngb at the cerebral level and secondarily the release in the plasma [24] [53]. In this case, this result suggests CmNgb as a biological element of monitoring, at least during the early and critical phase of stroke [11] [12] [13].…”
Section: Cmngb and Mean Of Age Of The Working Populationsupporting
confidence: 83%
“…In the human, two studies done by Jin et al in 2010 and 2013 had noted overexpression of Ngb, respectively in infarcted area of CI, and in peri-hematoma area during ICH secondary to a rupture of venous arterial malformations. According to them, these results supported the neuroprotective role of Ngb during ischemic events in the central nervous system, including stroke [13] [23] [24] [25] [26] [27]. Stroke (Cerebral infarction or CI, and intracerebral hemorrhage or ICH) is a common pathology in Africa World Journal of Neuroscience [28]- [33].…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…NGB was a novel discovered globin in 2000, which is an oxygen-binding protein that supplies oxygen to hypoxic tissue [66]. Evidence exists to support that NGB play an important role, which is upregulated after TBI to assist in promoting cell survival [67].…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia commonly occurs as a secondary injury response to TBI, NGB expression protects neurons from cell death and reactive oxygen species damage [30,31]. Multiple neuroprotective effects operate by different mechanisms, including inhibit calcium in ux, reduce cellular uptake of iron, copper, and zinc, suppress necrosis and apoptosis, and several studies suggest that NGB may positively affect TBI outcomes [32,33]. The reported results indicated that there was a late, but signi cant, increase in NGB mRNA expression 7 days post-TBI in WT mice and the subacute increase occurred later that were known to be upregulated at 3 days post-TBI [32].The previous work in the rat and mouse also showed increased NGB expression levels with peak time of 6 hours after TBI [34].…”
Section: Introductionmentioning
confidence: 99%